1965
DOI: 10.1111/j.1365-3180.1965.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

SOIL PLACEMENT STUDIES WITH EPTC AND OTHER CARBAMATE HERBICIDES ON AVENA SATIVA*

Abstract: Sludics wcrr conductpd to determine the cflTrct of soil placcmrni of EPTG. di-allaic and propham (IPCl on oau. A technique called the 'envelope method' vras used [o make pt.>isiblc the separate exposure of coleoplilc^, seed and roots of emerging oai ser^lingi to the various lierbirides. HPTC at 10 ppin, (ii-allatc at '20 pjini and propham at 3-0 ppm were all extremely toxin to oats through colcoptilc uptake. Penetration of roots intd treated soil, however, resulted in very little injury to the plant. Plants gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1966
1966
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Dawson (1963) showed similar results with EPTC. Appleby, Furtick & Fang (1965) reported similar effects with EPTC, di-allate and propham. Prendeville (1968) found, however, that in maize the shoot region around the growing point and crown root node was most sensitive to propham, chlorpropham and EPTC.…”
Section: Introductionmentioning
confidence: 55%
“…Dawson (1963) showed similar results with EPTC. Appleby, Furtick & Fang (1965) reported similar effects with EPTC, di-allate and propham. Prendeville (1968) found, however, that in maize the shoot region around the growing point and crown root node was most sensitive to propham, chlorpropham and EPTC.…”
Section: Introductionmentioning
confidence: 55%
“…This may be due to inherent resistance of sorghum roots to the herbicide, or to the fact that the bioassay was not extended over a longer period of time. Using radioactive EPTC, Yamaguchi (1961) and Appleby et al, (1965) found that absorption of this herbicide was by roots and shoots and translocation was upwards from roots to foliage and downward from foliage to roots. Appleby et al (1965) discovered no differences in uptake or metabolic degradation between the two zones; why EPTC was more toxic when the shoot rather than the roots was exposed to the compound is therefore still not clear.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published work on determination of the site of uptake of soilapplied herbicides by plants, has been conducted on carbamate-type herbicides such as isopropyl JV-phenylcarbamate (propham), 5-ethyl JVjV-dipropylthioIcarbamate (EPTC) and 5-2,3-dichloroallyl TVOV-di-isopropyl thi dear bam ate (diallate). Studies by Friesen, Banting & Walker (1962), Dawson (1963), and Appleby, Furtick & Fang (1965) on placement of these herbicides in soils indicated that they were primarily absorbed through the coleoptile of emerging grass seedlings. There was less effect on the plants when the root systems only were exposed to the herbicides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports (1)(2)(3)(4)(5)(6)(7) have been concerned with the site of uptake of EPTC in various plant species. In some species root exposure to the treated soil gave more injury than shoot exposure and in other species shoot exposure gave more injury (1,5).…”
Section: Introductionmentioning
confidence: 99%